Quantifying Modularity in the Evolution of Biomolecular Systems - Snel, Berend; Huynen, Martijn A. (Genome Research, 2004)
Functional modules are considered the primary building blocks of biomolecular systems. Here we study to what extent functional modules behave cohesively across genomes:That is, are functional modules also evolutionary modules? We probe this question by analyzing for a large collection of functional modules the phyletic patterns of their genes across 110 genomes. The majority of functional modules display limited evolutionary modularity. This result confirms certain comparative genome analyses, but is in contrast to implicit assumptions in the systems analysis of functional genomics data. We show that this apparent interspecies flexibility in the organization of functional modules depends more on functional differentiation within orthologous groups of genes, than on noise in the functional module definitions. When filtering out these sources of nonmodularity, even though very few functional modules behave perfectly modular in evolution, about half behave at least significantly more modular than a random set of genes. There are substantial differences in the evolutionary modularity between individual functional modules as well as between collections of functional modules, partly corresponding to conceptual differences in the functional module definition, which make comparisons between functional module collections biologically difficult to interpret. Analysis within one collection does not suffer from such differences, and we show that within the EcoCyc metabolic pathway database, biosynthetic pathways are evolutionarily more modular than catabolic pathways.
10.1101/gr.1969504